1984
DOI: 10.1002/j.0022-0337.1984.48.4.tb01775.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress management training for dental students

Abstract: Dental school and professional practice are well‐documented sources of stress. Although students and dentists risk developing stress‐related disorders, no empirically evaluated method for helping dental students cope with stress has been reported. A group of 17 dental students participated in a six‐session program that included instruction in self‐relaxation and time management; exercise and leisure planning; and cognitive modification techniques. From pre‐ to post‐training, subjects showed improvement on a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…Grandy et al. reported in detail various signs and symptoms of stress of students such as worry, tension, being upset, nervousness, discomfort, regret, lack of confidence, crying, indecision, unhappiness, avoidance, turmoil, insecurity, sadness, guilt, blame, irritability, apathy, weight loss, physical complaints and fatigue (10, 61).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Grandy et al. reported in detail various signs and symptoms of stress of students such as worry, tension, being upset, nervousness, discomfort, regret, lack of confidence, crying, indecision, unhappiness, avoidance, turmoil, insecurity, sadness, guilt, blame, irritability, apathy, weight loss, physical complaints and fatigue (10, 61).…”
Section: Resultsmentioning
confidence: 99%
“…Other signs and symptoms reported less frequently in the literature were low exam performance, where stressed dental students showed lower performances in exams than non‐stressed students (51). Other signs included hostility (39), social life effects (53), physical ill‐health (48), mental ill‐health (48), denial (54), substance use (54), gastrointestinal symptoms (61), sleeplessness (61) and psychosocial disturbance (4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for increased uncertainty and insecurity, 34 students may very well experience anticipatory anxiety because of it, although it generally tends to subside with experience. 36,37 Other authors have found that anticipatory anxiety sets in in the third term, when students are first exposed to patients. 11,12,16,18,20,23,35,38,39 Evaluation of the Sources of Stress in Dominican Dental Students: a cross-sectional study.…”
Section: Andmentioning
confidence: 99%
“…Whilst it is generally accepted that a variety of external factors may impact negatively on the stress experienced by dental students, there is also some evidence to show the contrary; that is, the external factors, for example exercise, can also help to protect students from stress and distress . Furthermore, it has been proposed that experiencing some stress within a dental course can be beneficial by giving a sense of purpose and achievement .…”
Section: Introductionmentioning
confidence: 99%